Influence of Blasting Vibration on Young Concrete Bridge: A Case Study of Yesanhe Super Large Bridge - Ming Chen; Jun Zhang; Wenbo Lu; Peng Yan; Ke Deng (Shock and Vibration)
Influence of blasting vibration on young concrete structure is an important issue in the field of hydropower engineering, transportation, and so forth. Based on influence of blasting excavation on concrete pouring progress of box girder in nearby Yesanhe Super Large Bridge, which is located in Hubei Province of China, a method combining field test and numerical simulation is used to study influence of blasting vibration on young concrete super large bridge. The results show that blasting excavation of nearby Yesanhe Hydropower Station induced vibration response on Yesanhe Bridge and peak particle velocity (PPV) on the bridge was quite small under test conditions. Monitoring data and numerical simulation both indicate that PPV of box girder is 1 to 4 times larger than that of pier foundation; with the extension of bridge cantilever casting section, velocity amplification factors of different parts of the box girder have different changes and duration of vibration in vertical direction increases. Three days after concrete pouring, the impact of concrete ageing on PPV and damage distribution of the bridge is not obvious. When vibration velocity of pier foundation is within 2 cm/s, the maximum tensile and compressive stress of box girder concrete are less than the tensile and compressive strength of concrete, so that blasting vibration unlikely gives impact on the safety of bridge.